Avaliação da eficiência do ultrassom no processo de separação de fases em água produzida e em emulsões sintéticas do tipo O/A - Ronchi, Renata Peterle (2014)
A major problem in the petroleum industries is related to the development of effective technologies for the wastewater treatment derived from the primary processing stage, which presents stable emulsions of oil in water (O/W). A methodology for the synthesis of O/W emulsions is tried. It runs a few tests with ultrasound equipment in order to evaluate the ability of this technique in phase separation and the reduction in the content of Oils and Grease (TOG). The most stable emulsion obtained was the 1% (w/w) O/W emulsion, without any addition of compounds. That emulsion was then employed in the tests developed with ultrasonic equipment with frequencies of 25, 35, 45 and 130 kHz at temperatures of 25 and 60 °C. The 20-minute exposure time and presence or absence of Raschig rings were assessed too. The use of ultrasound applied in synthetic emulsion appeared as a promising technique. It could remove about 70% of the xxvii oil content in the oil by applying frequencies of 35, 45 and 130 kHz at 60 °C with Raschig rings. The conditions of the best results were also selected for the study of produced water derived from the field A, but this time with shorter exposure time to ultrasound with more concentrated synthetic emulsions and colloidal particles, utilizing further materials like copper, PVC®, PTFE®, steel and polypropylene. Good results were obtained for 15-minute exposure time to ultrasound and denser materials such as copper and steel. TOG could reach values of up to 80% of reduction. The results for the other synthetic emulsions and produced water were worse than the 1 % (w/w) O/W emulsion, without acid, base or silica. Therefore, one can conclude this as an efficient laboratory method for oil/water phase separation and still fits a simple physical separation process with low cost, low dwell time and no need of chemical products.